2015
DOI: 10.1021/cm504413g
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Ge and Si on the Performances and Mechanism of the GexSi1–x Electrodes for Li Ion Batteries

Abstract: While silicon is attractive due to its high capacity, germanium possesses a superior electronic and ionic conductivity, and is able to support much higher cycle rates. In the present paper, we investigate the electrochemical performances of Ge x Si 1−x -based electrodes with x = 0, 0.25, 0.5, 0.75, and 1. The Ge x Si 1−x samples are easily prepared by short ball milling. X-ray diffraction (XRD), Raman spectroscopy, and scanning electron microscopy−energy-dispersive X-ray spectrometry confirm that Si/Ge solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 40 publications
4
35
2
Order By: Relevance
“…[13] Recently,i t has been demonstrated that the combination of Si and Ge (Si/ Ge) either by alloying Si with Ge (SiGe) or by employing SiGe heterostructures can take full advantages of the merits from these two materials with modified physicochemical properties and enhanced lithium-storage performance. [14][15][16][17][18][19] However,d ramatic volume changes associated with the lithium insertion and extraction reactions (up to 400 %) lead to pulverization of the Si/Ge based materials and thus poor cycling life of electrodes. [20] One typical approach to overcome this problem is the design and synthesis of complex micro-/nanostructured electrodes that can maintain their structural integration after many cycles.…”
mentioning
confidence: 99%
“…[13] Recently,i t has been demonstrated that the combination of Si and Ge (Si/ Ge) either by alloying Si with Ge (SiGe) or by employing SiGe heterostructures can take full advantages of the merits from these two materials with modified physicochemical properties and enhanced lithium-storage performance. [14][15][16][17][18][19] However,d ramatic volume changes associated with the lithium insertion and extraction reactions (up to 400 %) lead to pulverization of the Si/Ge based materials and thus poor cycling life of electrodes. [20] One typical approach to overcome this problem is the design and synthesis of complex micro-/nanostructured electrodes that can maintain their structural integration after many cycles.…”
mentioning
confidence: 99%
“…[1][2][3] Silicon (Si), germanium (Ge), tin (Sn), and aluminum (Al) all can alloy with Li at low electrochemical potentials relative to Li/Li+. 4,5 At the high end, Si can store more than 10 times the amount of Li than the state-of-the-art anode material, graphite, can store. 1 Unfortunately, these materials also undergo an approximately 300% volume expansion during the alloy process.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have taken several approaches to studying the material, including making powders of varying composition, growing thin films, in situ transmission electron microscopy (TEM) testing of single particles, computational simulation, and in situ atomic force microscopy (AFM) testing. 1,5,[7][8][9] The in situ AFM testing confers the benefits of visualizing nano-and microscale particles in conventional electrolytes with the ability to use conventional electrochemical testing.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For example, the low capacity of Ge is improved by alloying with Si, whereas the inferior Li-ion diffusivity (6.25 10 À12 cm 2 s À1 for Ge; 1.9 10 À14 cm 2 s À1 for Si) and poor electrical conductivity (2.1 S m À1 for Ge; 1.6 10 À3 S m À1 for Si) of Si are enhanced when alloyed with Ge. [8] In particular, extensive studies demonstrated that alloying Si with Ge provides an effective means to improve the capacity, cycling performance, and rate performance. [8] In particular, extensive studies demonstrated that alloying Si with Ge provides an effective means to improve the capacity, cycling performance, and rate performance.…”
mentioning
confidence: 99%